Perbandingan Sistem Administrasi Negara Indonesia Dengan Filipina - Leksono, Totok Minto; Andriyanti, Talitha (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
As a system, this is of course closely related to the basic assumptions that serve as a reference for the framework of state administration. Every country, whether it is a developed or developing country, a large or a small country, must have its own administration system which is adapted to the situation and conditions of each country. The state administration system consists of sub-systems consisting of humans and/or non-humans (non-humans) that are organized and regulated in such a way that these sub-systems can act as one unit in achieving goals, objectives and targets or final results in accordance with identity. In a democratic country, of course, there is a constitutional system or order and there is a separation of powers. This is related to the institutions that exist in a sovereign country, namely the state of Indonesia and the Philippines. Given that the countries of Indonesia and the Philippines are countries based on democratic law, the existence of representative institutions can be an alternative as well as a liaison between the state and its people or community aspirators so that a sovereign society can be achieved.